TRANSPARANSI INFORMASI SITUS WEB INSTITUT PEMERINTAHAN DALAM NEGERI DALAM PROSES PENERIMAAN PRAJA IPDN - Ayu Widowati Johannes (Institut Pemerintahan Dalam Negeri, 2017)
The perspective of government communication is a picture of future communications that can be applied to bring about change and find the most efficient formula in its implementation. Implementation of the concept of good governance through information transparency can support the implementation of better governance activities. Change of government communication paradigm from old structure system, culture and procedure into better structure, culture and procedure. The change is seen in the higher public confidence in IPDN Selection of Prospective Admission (SPCP) online. With increasing public trust, will increase trust in the Institute of Domestic Government in the selection of candidates. The transparency of IPDN information ultimately supports the implementation of good governance in Indonesia in general.